Broadcasters' rights in the digital era : copyright concerns on live streaming - Sakthivel, M. (Law teacher) (Brill Nijhoff, 2020)
"In Broadcasters' Rights in the Digital Era, Sakthivel provides a cogent understanding into a hitherto unchartered territory on the applicability of copyright law on the live streaming of 'entertainment content'- an emerging medium of communication. The book examines in exhaustive breadth the scope of broadcasters' neighbouring rights under the copyright regime in the light of technological advancements vis-à-vis authors' right and explores the experiences of EU & USA and then suggests suitable changes to the Indian Copyright regime. Sakthivel employs technological analysis and existence of differential market for different mediums to substantiate the relationship of live streaming and the copyright regime"--